Advanced strategies for optimization of primary nutrients requirement in rice-A review - Lalichetti, Sagar; Maitra, Sagar; Singh, Sultan; Masina, Sai Ram (Plant Science Today, 2024)
The Green Revolution led to India's food independence mostly through the inclusion of supply-driven technologies, such as the introduction of high-yielding cultivars, improved access to water, agrochemicals, and mechanization. The present and future needs target agricultural sustainability without endangering the ecosystem. In this regard, the adoption of precision agriculture is required to meet this expected objective. In developed nations, precision farming has already experienced tremendous growth. However, precision farming methods have taken a while for emerging nations in Asia to comprehend, create, and embrace. Moreover, precision farming is frequently misunderstood as a sophisticated technological intervention intended for extensive agricultural fields. However, it is essentially a science that involves using the "right input" in the "right quantity," at the "right time," and in the "right place," to improve input use efficiency. In the case of primary nutrients such as nitrogen, phosphorus, and potassium, so-called recommendations for nutrient management based on soil tests have improved food grain output which increased the nutrient use efficiency up to a certain extent. Moreover, the recommendations are made for a given agroclimatic region and crops irrespective of site-specific soil fertility, cultivars, and agronomic management levels resulting in excess or scanty use to crop needs. At this juncture, assessing the nutritional requirements of plants proves to be a superior method, as it takes into account the cumulative impact of nutrient availability from various sources on plant growth at any specific stage, making it a reliable indicator of nutrient accessibility. Rice, the most important food crop, is grown in diverse agroclimatic regions at different management levels. Hence, there is an urgent need to adopt a precision nutrient management strategy to optimize the yield output. The article offers an overview of several precision instruments available for managing nutrients at specific sites and aids in choosing the most appropriate one for each circumstance.